Clinical Outcomes and Prognostic Factors of Salvage Treatment for Local Lymph Node Recurrence After Radical Resection of Oesophageal Carcinoma - Gu L; Liu Y; Ye H; Gao F; Yin X; Zhao Y; Tian Y (Cancer Management and Research, 2021)
Liang Gu,1,2 Yangchen Liu,2 Hongxue Ye,2 Fei Gao,2 Xiaoxiang Yin,2 Ying Zhao,2 Ye Tian1 1Department of Radiation Oncology, The Second Affiliated Hospital of Soochow University, Su Zhou, 215004, Jiang Su Province, People’s Republic of China; 2Department of Radiation Oncology, Taixing People’s Hospital, Tai Xing, 225400, Jiang Su Province, People’s Republic of ChinaCorrespondence: Ye TianDepartment of Radiation Oncology, The Second Affiliated Hospital of Soochow University, 1005 Sanxiang Road, Su Zhou, 215004, Jiang Su Province, People’s Republic of ChinaEmail dryetian@126.comBackground: There are no standard therapeutic strategies for local lymph node (LN) recurrence after radical resection of oesophageal squamous cell carcinoma (ESCC), and prognostic risk factors remain controversial. We assessed clinical outcomes and prognostic factors of chemoradiotherapy (CRT) or radiotherapy (RT) for LN recurrence of ESCC after curative resection.Methods: A total of 117 ESCC patients with LN recurrence after radical resection receiving salvage treatment at our hospital were retrospectively reviewed from 2014 to 2017. Overall survival (OS) was estimated using the Kaplan–Meier method; clinical characteristics were assessed using the Log rank test in the univariate analysis. Multivariate prognostic analysis was performed using the Cox proportional hazard model.Results: With a median follow-up of 19 months, the 1-, 2- and 3-year OS rates were 75.2%, 40.2% and 27.4%, respectively. The median survival time (MST) was 19.0 months. On univariate analysis for OS, pathological TNM stage, number of LN metastasis, LN maximum (Max) diameter, salvage treatment mode and tumor response were significantly associated with OS (P = 0.0074, P = 0.015, P = 0.0011, P = 0.028, P < 0.000, respectively). On multivariate analysis, tumor response [Response vs No-response hazard ratio (HR), 2.43; 95% confidence interval (CI), 1.53– 3.90, P < 0.000] and LN Max diameter (≤ 28 mm vs > 28 mm HR, 2.07; 95% CI, 1.33– 3.32, P = 0.012) were independent prognostic factors.Conclusion: Salvage CRT or RT was safe and effective for treating LN recurrence after radical resection in ESCC. Patients with the small LN Max diameter (≤ 28 mm) and obtained response after salvage therapy appeared to achieve long-term OS.Keywords: oesophageal cancer, lymph node recurrence, chemoradiotherapy